Nilai Kerugian Ekonomi Lingkungan Akibat Kebakaran Hutan dan Lahan Gambut di Kota Banjarbaru - Rimbawan, Gema Aji; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to estimate environmental, economic losses value because of forest and peatland fires in Banjarbaru City and assess the government's prevention efforts. This study is a quantitative descriptive study by processing the data of the forest and the peatland fires. The data analysis technique used uses the total economic value (TEV) approach, where the used variables are biodiversity damage value, carbon release value, nutrient loss value, and water regulation value. The types of user data are secondary data which is time series among 2018-2019, and primary data regarding the prevention efforts also support these. The results of this study indicate that the total environmental, economic losses value due to forest peatland fires in Banjarbaru City in 2018 reached Rp.6.214.204.338, and in 2019 reached Rp.6.904.137.284. Thus, the occurrence of these fires extremely affects the environmental damage. TheSome prevention efforts have been carried out, such as doing integrated coordination meetings, mapping fire-prone areas, and doidirectingcialization to the public related to the danger of forest fire with its temporary countermeasures, including appeals regarding appeals fie forest through mass media.